Cardiovascular complications of COVID-19 - I. A. Kozlov; I. N. Tyurin (Вестник анестезиологии и реаниматологии, 2020)
The objective: based on publications to provide up-to-date information on the frequency, basic variants and predictive significance of cardiovascular complications of the coronavirus infection caused by SARS-CoV-2.Results: the article identifies variants of cardiovascular disorders in COVID-19 caused by various comorbidities in particular hypertension, specific virus-associated myocardial damage, and side effects of medications. It analyzes the role of angiotensin-converting enzyme 2 type II receptors during infection with the coronavirus and potential changes in the renin–angiotensin–aldosterone system including in patients receiving angiotensin-converting enzyme inhibitors or blockers of angiotensin receptors. The data on the frequency and prognostic role of arrhythmias, virus-associated myocardial damage and heart failure, the risk of ischemia, and myocardial infarction are presented. The adverse cardiovascular events of drugs of different groups prescribed for treatment of COVID-19 and possible drug interactions are described. The current recommendations for cardiotonic and cardioprotective therapy in patients with cardiovascular complications are analyzed.Conclusion. The SARS-Cov-2 virus has a pronounced cardiac tropic effect which requires maximum cardiac alertness in the treatment of patients in this category, timely use of electrocardiography, echocardiography, control of biomarkers of myocardial damage and tension, as well as a reasonable use of cardiotonic and cardioprotective drugs.